2019
DOI: 10.1016/j.jtho.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Surgery in Large Cell Lung Neuroendocrine Cancer

Abstract: Introduction: There are limited small, single-institution observational studies examining the role of surgery in large cell neuroendocrine cancer (LCNEC). We investigated the outcomes of surgery for stage I to IIIA LCNEC by using the National Cancer Database. Methods: Patients with stage I to IIIA LCNEC were identified in the National Cancer Database (2004-2015) and grouped by treatment: definitive chemoradiation versus surgery. Overall survival, by stage, was the primary outcome. Outcomes of surgical patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
(33 reference statements)
3
29
1
Order By: Relevance
“…The predominance of men was also reported in other studies and R0 resection was observed in 90-99.2% [2,20,28]. Other authors have also confirmed that the most frequently used surgery option was also lobectomy [5,25,26]. All analyzed patients, whose smoking status was known, were smokers.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The predominance of men was also reported in other studies and R0 resection was observed in 90-99.2% [2,20,28]. Other authors have also confirmed that the most frequently used surgery option was also lobectomy [5,25,26]. All analyzed patients, whose smoking status was known, were smokers.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results (64.5%) were achieved in a single-institution retrospective analysis conducted on 125 patients [36]. In USA Raman et al [26] performed 5-year survival (50%, 45%, and 36% for CS I, II, and IIIA, respectively) using a largest cohort on the world (>6000 patients). Similar to Eichhorn et al [30], who determined that advanced nodal status was significantly associated with poor outcome, in our analysis, LCNEC patients treated with resection who did not show lymph node metastasis had better prognosis (OS and TTR) in comparison with N+ patients, although the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations